Biofilm growth and microbial contamination of dental unit waterlines at Kuwait University dental center - Hussain Akbar, Jaber; Behbehani, Jawad; Karched, Maribasappa (Frontiers in Oral Health, 2023)
Biofilm formation in dental unit waterlines and the resulting microbial contamination of the water in the system has become a significant problem. Contaminated water in the dental units is a major concern in dental clinics due to potential risk of causing infections particularly in elderly and immunocompromised patients. The aim of this study was at first to determine microbial contamination of the dental unit waterlines and then to study the efficacy of a comprehensive disinfection protocol on decreasing the microbial load. Water samples were collected before and after disinfection procedure from handpieces and water storage bottles from the dental units, a small 1-cm tubing was cut from each unit and subjected to microbiological culture on different growth media. Identification of the predominant species was achieved by 16S rRNA gene sequencing. Microbial growth was observed in samples collected from all dental units. Upon disinfection procedure, microbial contamination in the water samples and in the tubing surfaces was significantly reduced (P > 0.05). 16S rRNA gene sequencing revealed the presence of several species belonging to the genera Staphylococcus, Corynebacterium and Roseomonas, some of which are implicated in human infections. Aggravation of the biofilm growth on the tubing surfaces and the microbial contamination in the water can be effectively controlled by implementing appropriate and routine disinfection protocols. This may help protect the dental unit staff and the patients being exposed to the risk of infections.